Multimodal Interactions for Linking Everyday Presentations in a Ubiquitous Computing Infrastructure - Macedo, Alessandra A.; Camacho-Guerrero, José; Cattelan, Renan G.; Inácio Jr., Valter; Pimentel, Maria G. C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2010)
Live presentations can be captured in instrumented places generating documents with the talk. A presentation is normally related to others as well as to documents. Therefore, linking of the related documents, before and after a live presentation takes place, can be useful when lecturers are interesting in knowing more about his talk. Moreover, the availability of linking during the presentation provides a unique opportunity for linking in the live context itself. On the one hand, it is interesting that the creation of links occurs automatically given the amount and diversity of information. On the other hand, the evaluation of the possibilities of links identified by algorithms can be a burden when the user does not have the focus of attention on the associated task. We propose that well-known Web interacting operations be used to identify links. The operations should be made available before, during and after live presentation and in any case the user should attach relevant results as annotations. We present the model and associated implementation. The activation of the operations can be done automatically by multimodal interactions, typing and browsing.